Advanced Ultrasound Techniques for Neuroimaging in Pediatric Critical Care: A Review - Colbey W. Freeman; Misun Hwang (Children, 2022)
Because of its portability, safety profile, and accessibility, ultrasound has been integral in pediatric neuroimaging. While conventional B-mode and Doppler ultrasound provide anatomic and limited flow information, new and developing advanced ultrasound techniques are facilitating real-time visualization of brain perfusion, microvascular flow, and changes in tissue stiffness in the brain. These techniques, which include contrast-enhanced ultrasound, microvascular imaging, and elastography, are providing new insights into and new methods of evaluating pathologies affecting children requiring critical care, including hypoxic–ischemic encephalopathy, stroke, and hydrocephalus. This review introduces advanced neurosonography techniques and their clinical applications in pediatric neurocritical care.